Abstract 065: Advancing Stroke Care Services through Collaborative Efforts: Mission Thrombectomy Surveys of Slovenia - Igor Rigler; Senta Frol; Janja Pretnar Oblak; Zoran Milošević (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Acute stroke care must always be improved because stroke is still a leading cause of mortality and adult‐onset disability. The Mission Thrombectomy Slovenia Regional Committee (RC) has established a forward‐thinking initiative to improve stroke treatment services in response to this challenge. With a focus on showcasing the complete picture of stroke systems and identifying areas for improvement to achieve better patient outcomes and increase accessibility to mechanical thrombectomy (MT) treatments in Slovenia, this partnership aims to conduct extensive surveys, analyses, and propose a roadmap to overcome obstacles and optimize the stroke care ecosystem. The SVIN Mission Thrombectomy Slovenia Regional committee (RC) comprises distinguished experts, including Zoran Miloševič as Neurointerventional co‐chair, and Senta Frol and Janja Pretnar Oblak as stroke co‐chairs, respectively, and Igor Rigler as ER co‐chair, whose expertise and collaborative efforts form the backbone of this initiative. Methods As an initial step, we have commenced surveys with UMC Ljubljana, Slovenia. UMC Ljubljana, as a Mechanical Thrombectomy Center, has demonstrated consistent growth in the number of procedures conducted. There is a projection of 180 procedures in 2023, an increase from 135 in 2021 and 109 in 2022. The increased projected procedure volume indicates the hospital's proactive approach in delivering cutting‐edge stroke treatments. A pivotal aspect of UMC Ljubljana's stroke care model lies in its advanced imaging capabilities, including CTA/CTP and MRI/MRP, enabling precise and swift diagnoses, fostering better treatment planning, and optimizing patient outcomes. Furthermore, the presence of a well‐equipped Angio suite, staffed with competent MT operators, ensures seamless execution of interventional procedures. Results The collaboration's future vision involves conducting surveys and analyzing data to identify barriers to MT access, streamlining the patient journey, and improving overall stroke care efficiency. The ongoing efforts of building a Stroke Registry at UMC Ljubljana will enable in‐depth analysis, fostering continuous evolution in stroke care practices. Additionally, investments in Intermediate/Step down care and Telemetry beds will play a vital role in strengthening the continuum of care, enabling smooth patient transitions, and reducing potential delays in treatment. Healthcare practitioners' awareness for stroke triage and Physician Training emerge as the most impactful Thrombectomy Patient Health Initiatives. By prioritizing these initiatives, UMC Ljubljana and Mission Thrombectomy aim to foster early recognition, prompt treatment, and streamlined care for stroke patients. Conclusion In conclusion, the collaborative efforts of UMC Ljubljana and Mission Thrombectomy Slovenia RC are poised to elevate stroke care and MT services through data‐driven analysis and the proposed roadmap. By incorporating future surveys and continuous improvement strategies, the collaboration aims to create a paradigm shift in stroke care, ensuring accessible, efficient, and optimized services to patients in need. Moving forward, we will continue to conduct surveys within the current EVT and stroke centers examining the calculated MT Operator availability (MTOA), MT Center availability (MTCA), and MT Access Rate (MTAR) scores to identify the current barriers to increase access to mechanical thrombectomy.